Water markets' promise: the Murray–Darling Basin. (1st December 2022) - Debaere, Peter; Li, Tianshu
Abstract: The very advanced and well-designed water markets in the Murray– Darling Basin are the result of long and complex reforms. Using state-level export data for agricultural and manufacturing sectors, we study the impact of water markets on the allocation of water through the first (1994–2006) and second reform periods (2007–2015), relative to when the markets' foundations were laid (1988–1993). We find water markets trigger a shift away from the water-intensive (less water-productive) sectors that is most pronounced during droughts in the first reform period. However, improvements in technology and techniques that reduce water intensity (increase water productivity) partially offset such a shift. We also document an inter-sectoral shift of activity between agriculture and manufacturing, as well as address some recent criticisms of water markets' effectiveness.